Chemical Remediation of Pharmaceutical Pollutants in Contaminated Soils: A Review of Oxidation-Based Approaches - Jayasekara, Upeksha Gayangani; Siganul, Aimie Peace; Premarathna, Kadupitige Shashikala Dilrukshi (Industrial and Domestic Waste Management, 2025)
The objective of this study is to develop effective chemical treatment methods to break down stubborn pharmaceutical pollutants in contaminated soil, enhancing its quality and reducing environmental risks. Numerous pharmaceuticals, which are substances used to cure or prevent illnesses in both humans and animals, are classified as pollutants of increasing concern because of their extensive environmental dispersion and their negative effects on populations. This is due to the constant discharge of sludge and effluent from wastewater treatment plants, which happens far more quickly than the removal of pharmaceuticals; they are frequently discovered in soils at considerable concentrations. Conventional wastewater treatment is unable to effectively remove pharmaceuticals from influent streams or biosolids, despite the fact that they are often present at low ambient quantities. Furthermore, through surface runoff and leaching, the application of animal manure to the soil can cause pharmaceuticals to contaminate the soil. Adsorption to soil colloids and degradation through the soil profile are some of the mechanisms that influence the behaviour and fate of pharmaceuticals in soils. The primary factor influencing how much organic matter is absorbed by plant roots is the sorption of pharmaceuticals in soils. This pharmaceutical pollutant in contaminated soil can lead to a negative impact on human and soil health. Therefore, remediation techniques such as chemical oxidation, soil washing, bioremediation, and phytoremediation should be used to reduce the pharmaceutical pollutants in the contaminated soil.